The output gap, the labor wedge, and the dynamic behavior of hours - Luca Sala; Ulf Söderström; Antonella Trigari (Sveriges Riksbank, 2010)
We use a standard quantitative business cycle model with nominal price and wage rigidities to estimate two measures of economic ineffciency in recent U.S. data: the output gap - the gap between the actual and effcient levels of output - and the labor wedge - the wedge between households' marginal rate of substitution and firms' marginal product of labor. We establish three results. (i ) The output gap and the labor wedge are closely related, suggesting that most ineffciencies in output are due to the ineffcient allocation of labor. (ii ) The estimates are sensitive to the structural interpretation of shocks to the labor market, which is ambiguous in the model. (iii ) Movements in hours worked are essentially exogenous, directly driven by labor market shocks, whereas wage rigidities generate a markup of the real wage over the marginal rate of substitution that is acyclical. We conclude that the model fails in two important respects: it does not give clear guidance concerning the effciency of business cycle uctuations, and it provides an unsatisfactory explanation of labor market and business cycle dynamics.
Keywords: E32; E24; E52; 330; Business cycles; Effciency; Labor markets; Monetary policy; Konjunktur; Geldpolitik; Arbeitsmarkt; Wirtschaftspotenzial; Theorie; USA